Natural killer and dendritic cells collaborate in the immune response induced by the vaccine against uterine cervical cancer. Issue 12 (7th November 2014) - Langers, Inge; Renoux, Virginie; Reschner, Anca; Touzé, Antoine; Coursaget, Pierre; Boniver, Jacques; Koch, Joachim; Delvenne, Philippe; Jacobs, Nathalie
Abstract : Virus‐like particles (VLPs) of human papillomavirus (HPV) are used as a vaccine against HPV‐induced cancer, and recently we have shown that these VLPs are able to activate natural killer (NK) cells. Since NK cells collaborate with dendritic cells (DCs) to induce an immune response against viral infections and tumors, we studied the impact of this crosstalk in the context of HPV vaccination. NK cells in the presence of HPV‐VLPs enhanced DC‐maturation as shown by an upregulation of CD86 and HLA‐DR and an increased production of IL‐12p70, but not of the immunosuppressive cytokine IL‐10. This activation was bidirectional. Indeed, in the presence of HPV‐VLPs, DCs further activated NK cells by inducing the upregulation of cell surface activation markers (CD69 and HLA‐DR). The function of NK cells was also improved as shown by an increase in IFN‐γ secretion and cytotoxic activity against an HPV + cell line. This crosstalk between NK cells and DCs needed CD40 interaction and IL‐12p70 secretion, whereas NKG2D was not implicated. Our results provide insight into how VLPs interact with innate immune cells and how NK cells and DCs play a role in the immune response induced by this vaccine agent.